Center of gravity estimation using a reaction board instrumented with fiber Bragg gratings - Rui Oliveira; Paulo Roriz; Manuel B. Marques; Orlando Frazão (Photonic Sensors, 2018)
Abstract The purpose of the present work is to construct a reaction board based on fiber Bragg gratings (FBGs) that could be used for estimation of the 2D coordinates of the projection of center of gravity (CG) of an object. The apparatus is consisted of a rigid equilateral triangular board mounted on three supports at the vertices, two of which have cantilevers instrumented with FBGs. When an object of known weight is placed on the board, the bending strain of the cantilevers is measured by a proportional wavelength shift of the FBGs. Applying the equilibrium conditions of a rigid body and proper calibration procedures, the wavelength shift is used to estimate the vertical reaction forces and moments of force at the supports and the coordinates of the object’s CG projection on the board. This method can be used on a regular basis to estimate the CG of the human body or objects with complex geometry and density distribution. An example is provided for the estimation of the CG projection coordinates of two orthopaedic femur bone models, one intact, and the other with a hip stem implant encased. The clinical implications of changing the normal CG location by means of a prosthesis have been discussed.